Oscillatory Brain Dynamics during Sentence Reading: A Fixation-Related Spectral Perturbation Analysis - Vignali, Lorenzo; Himmelstoss, Nicole A.; Hawelka, Stefan; Richlan, Fabio; Hutzler, Florian (Frontiers in Human Neuroscience, 2016)
The present study investigated oscillatory brain dynamics during self-paced sentence-level processing. Participants read fully correct sentences, sentences containing a semantic violation and “sentences” in which the order of the words was randomized. At the target word level, fixations on semantically unrelated words elicited a lower-beta band (13-18 Hz) desynchronization. At the sentence level, gamma power (31-55 Hz) increased linearly for syntactically correct sentences, but not when the order of the words was randomized. In the 300 to 900 ms time window after sentence onsets, theta power (4-7 Hz) was greater for syntactically correct sentences as compared to sentences where no syntactic structure was preserved (random words condition). We interpret our results as conforming with a recently formulated predictive-coding framework for oscillatory neural dynamics during sentence-level language comprehension. Additionally, we discuss how our results relate to previous findings with serial visual presentation versus self-paced reading.